(untitled) (Hematology Meeting Reports, 2009)
Acute myeloid leukaemia (AML) occurring in children and younger adults is commonly associated with reciprocal balanced chromosomal translocations, which lead to the formation of chimaeric proteins that play a key role in mediating the leukaemic phenotype (reviewed 1).